2020
DOI: 10.3390/s20195698
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of the Impact of Microwave Ablation on the Dielectric Properties of Breast Tissue

Abstract: Percutaneous microwave ablation (MWA) is a promising technology for patients with breast cancer, as it may help treat individuals who have less aggressive cancers or do not respond to targeted therapies in the neoadjuvant or pre-surgical setting. In this study, we investigate changes to the microwave dielectric properties of breast tissue that are induced by MWA. While similar changes have been characterized for relatively homogeneous tissues, such as liver, those prior results are not directly translatable to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…Treatment of NPM by US-guided MWA directly inactivates the protein in inflammatory lesions by applying a high temperature and coagulates necrotic tissue. It has the advantages of a short treatment time and a rapid effect [32,33]. US guidance is used to estimate the ablation range.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of NPM by US-guided MWA directly inactivates the protein in inflammatory lesions by applying a high temperature and coagulates necrotic tissue. It has the advantages of a short treatment time and a rapid effect [32,33]. US guidance is used to estimate the ablation range.…”
Section: Discussionmentioning
confidence: 99%
“…These treatments affect not only the tumor but also the adjacent breast and adipose tissue. [3] Yang et al [1] applied 755 MWA procedures to a series of 440 patients and reported 100% success rates. The volume response rate was 78.8% in the 6 th month follow-up, and 97.9% in the 12 th month.…”
Section: Discussionmentioning
confidence: 99%
“…El tumor absorbe la energía, e induce los efectos citotóxicos del calor, lo que resulta en la desnaturalización de proteínas y la necrosis de la coagulación. Los resultados de la MWA mamaria muestran una reducción en el volumen y la palpabilidad de las lesiones y resultados cosméticos satisfactorios (Neira et al, 2020).…”
Section: Ablación Por Microondasunclassified